Physical and Psychological Preparation in Preparing for Childbirth - Ritonga, Fitriana; Sebayang, Welina; T. Bolon, Christina Magdalena; Nisa, Khairun (CV. Devitara, 2023)
The health status of a country can be determined by high or low maternal mortality rates and newborn mortality rates. Maternal Mortality Rate (MMR) is an indicator of the success of a country's health services. Every day more than 850 women die due to complications during pregnancy and childbirth. There are several things that mothers and families must prepare for when facing childbirth. Physical and psychological preparation is one of the many preparations that mothers must pay attention to. The aim of this research is to determine the mother's physical and psychological preparation in preparing for childbirth. Research method: This type of research is qualitative descriptive research. Data is collected through interviews which will then be observed and grouped according to research themes and sub-themes. The research was conducted in the Labuhanbilik city area with the research implementation period starting from 21 September 2023 to 6 January 2024. The research results consisted of 2 themes, namely 1)the experience of physical preparation that the mother does in preparing for childbirth, 2) the experience of psychological preparation that the mother does in preparing for childbirth. Each theme has sub themes.Conclusion: Mothers who have experienced childbirth say they have made various preparations for the upcoming birth, such as taking leisurely walks, eating nutritious food, carrying out pregnancy checks, and getting support from their husbands and family.